Prolonged Chronic Consumption of a High Fat with Sucrose Diet Alters the Morphology of the Small Intestine - Sferra, Roberta (Int J Mol Sci, 2021)
(1) The high-fat diet (HFD) of western countries has dramatic effect on the health of several organs, including the digestive tract, leading to the accumulation of fats that can also trigger a chronic inflammatory process, such as that which occurs in non-alcohol steatohepatitis. The effects of a HFD on the small intestine, the organ involved in the absorption of this class of nutrients, are still poorly investigated. (2) To address this aspect, we administered a combined HFD with sucrose (HFD w/Suc, fat: 58% Kcal) regimen (18 months) to mice and investigated the morphological and molecular changes that occurred in the wall of proximal tract of the small intestine compared to the intestine of mice fed with a standard diet (SD) (fat: 18% Kcal). (3) We found an accumulation of lipid droplets in the mucosa of HFD w/Suc-fed mice that led to a disarrangement of mucosa architecture. Furthermore, we assessed the expression of several key players involved in lipid metabolism and inflammation, such as perilipin, leptin, leptin receptor, PI3K, p-mTOR, p-Akt, and TNF-α. All these molecules were increased in HFD mice compared to the SD group. We also evaluated anti-inflammatory molecules like adiponectin, adiponectin receptor, and PPAR-γ, and observed their significant reduction in the HFD w/Suc group compared to the control. Our data are in line with the knowledge that improper eating habits present a primary harmful assault on the bowel and the entire body’s health. (4) These results represent a promising starting point for future studies, helping to better understand the complex and not fully elucidated spectrum of intestinal alterations induced by the overconsumption of fat.